1982
DOI: 10.1007/bf00215708
|View full text |Cite
|
Sign up to set email alerts
|

Transmission and scanning electron-microscopic observations on tanycytes in the mediobasal hypothalamus and the median eminence of adrenalectomized rats

Abstract: Tanycytes in the median eminence (ME) of the rat exhibit morphological features suggesting their possible participation in transport phenomena. After adrenalectomy, which modifies the hypothalamo-hypophyseal axis, they undergo morphological changes characterized by an accumulation of lipid droplets, an increased number of bleb-like protrusions at their apex, as well as an increased pinocytosis of intraventricularly injected horseradish peroxidase (HRP). In addition, after adrenalectomy an increased number of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…They do not incorporate horseradish peroxidase injected intraventricularly, suggesting that they are intracellular structures (Brion et al 1982). Transmission electron-microscopic studies (Brion et al 1982;Bodoky et al 1979;Amat et al 1999) indicate that these large cisternae are localized within tanycytes. The availability of a specific immunological marker for tanycytes has allowed us, in the present investigation, to demonstrate that many of these vacuoles are, indeed, within basal processes of tanycytes labeled with anti-P85.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They do not incorporate horseradish peroxidase injected intraventricularly, suggesting that they are intracellular structures (Brion et al 1982). Transmission electron-microscopic studies (Brion et al 1982;Bodoky et al 1979;Amat et al 1999) indicate that these large cisternae are localized within tanycytes. The availability of a specific immunological marker for tanycytes has allowed us, in the present investigation, to demonstrate that many of these vacuoles are, indeed, within basal processes of tanycytes labeled with anti-P85.…”
Section: Discussionmentioning
confidence: 96%
“…Brion et al 1982). Transmission electron-microscopic analysis clearly showed that these vacuoles are intracellular structures located within dilated portions of processes most likely corresponding to basal processes of tanycytes (Fig.…”
Section: Organ Culture Of Bovine Median Eminencementioning
confidence: 99%
“…Wittkowski 48 and Kobayashi et al90 described neuroglial cells in the median eminence characterised by a well-developed Golgi apparatus, numerous mitochondria and abundant lipid droplets (0.5-2 μm) localised in the perikaryon and cell processes. After adrenalectomy and castration, the number of lipid bodies in the median eminence neuroglial cells increases 49,90,134. We have recently revisited the ultrastructure of pituicytes of the median eminence.…”
mentioning
confidence: 99%
“…Further, we suspect that the cisterns that are normally present within the median eminence predispose this region to vacuolation. Tangential evidence for this hypothesis is supported by a study whereby adrenalectomy in adult rats increased the abundance of hypothalamic cisterns (40). Since adrenalectomy causes low serum sodium, this observation is consistent with our findings in the present hyponatremic model.…”
Section: Discussionmentioning
confidence: 98%